A gangue-slag-fly ash based alkali activated composite material and preparation method thereof
By using high-temperature calcined coal gangue powder, fly ash and slag, coal gangue-slag-fly ash base excitation composite materials, the problem of insufficient mechanical properties in the existing technology is solved and high strength is achieved , good ductility and excellent mechanical properties.
Patent Information
- Application Number
- CN202410898696.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-05
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-07-05
AI Technical Summary
In the prior art, when using coal gangue, fly ash and slag as gelling materials, the mechanical properties are insufficient and the utilization rate is not high.
Coal gangue powder, fly ash and slag are used as the main raw materials, combined with quartz sand, alkali trigger, fiber, retarder and water, to prepare a coal gangue-slag-fly ash base excitation composite material. Coal gangue powder is used after high-temperature calcination, and it has a pozzolanic ash effect and a micro aggregate effect, enhancing the mechanical properties of the composite material.
The ultimate strength, elastic modulus, fracture toughness and crack control capabilities of the composite material are improved, the shaft pulling and axial compression performance is enhanced, and the ductility and post-peak ductility are improved.
Smart Images

Figure CN118851642B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of building materials, and in particular relates to a gangue-slag-fly ash based alkali-activated composite material and a preparation method thereof. Background Art
[0002] Gangue is a kind of industrial solid waste produced during coal mining, washing and processing, accounting for 10-25% of the total coal. The carbon emission risks of gangue itself include direct risks and indirect risks. Even though gangue is currently being reused in thermal power generation, preparation of ceramsite, chemical raw materials and building materials, the utilization rate is not high. In addition, when gangue is used as coarse aggregate for pavement concrete, as the amount of gangue increases, the strength and elastic modulus of concrete will decrease, and the abrasion resistance, impermeability and freeze-thaw resistance will seriously deteriorate.
[0003] Alkali-activated materials (AAM) are a type of building material that is mainly composed of natural minerals or industrial waste residues (such as kaolin, slag, fly ash, silica fume, steel slag, etc.) containing aluminum silicates with a certain rapid cooling and heating history and an alkali activator. It can maximize the use of various industrial by-products and does not require the use of silicate cement (which releases a large amount of carbon dioxide during its production process), thereby reducing the use of ordinary silicate cement that releases a large amount of carbon dioxide during its preparation process. It is an environmentally friendly material. However, in terms of AAM, most of the research focuses on fly ash and slag as cementitious materials, and there is no research on AAM of coal gangue-fly ash-slag ternary cementitious materials.
[0004] Therefore, how to use coal gangue, fly ash and slag as cementitious materials to prepare alkali-activated materials with excellent mechanical properties has become a technical problem that urgently needs to be solved in this field. Summary of the invention
[0005] In order to solve the above technical problems, the present invention proposes a gangue-slag-fly ash based alkali activated composite material and a preparation method thereof.
[0006] To achieve the above object, the present invention provides the following technical solutions:
[0007] The present invention provides a gangue-slag-fly ash-based alkali-activated composite material. The raw materials for preparing the gangue-slag-fly ash-based alkali-activated composite material include gangue powder, fly ash, slag, quartz sand, alkali activator, fiber, retarder and water.
[0008] The coal gangue powder, fly ash and slag constitute the cementitious material; the cementitious material comprises 2.5-12% of coal gangue powder, 52-58.3% of fly ash and 36.5-43.2% of slag in terms of mass percentage.
[0009] The gangue powder in the present invention has a volcanic ash effect and a micro-aggregate effect, which not only increases the number and bonding energy of hydration products in the composite material, makes a large number of pores tend to "spherical" or "arched" stress characteristics, and enhances the stress characteristics of the internal pores, but also the addition of gangue powder helps to fill the gap between the fiber and the matrix, so that in the process of crack expansion to instability, the bonding force between the fiber and the matrix is greater than the tensile capacity of the fiber, so the fiber is mainly in a fracture failure mode, and the fiber consumes more energy in the gradual fracture process, thereby effectively improving the ductility of the composite material. Slag has a high reactivity and can form a denser matrix in an alkaline environment, which improves the bonding force between the matrix and the fiber, reduces the proportion of the fiber pull-out failure mode, and thus improves the axial tensile limit strain of the composite material. Fly ash and gangue powder generate a large amount of Al-SH and NASH gel under the action of an alkali activator, and then interweave with a small amount of CASH generated by slag to form a better network structure, which together play a good synergistic role and improve the mechanical properties of the composite material.
[0010] The addition of coal gangue powder in the present invention can improve the ultimate strength, elastic modulus, fracture toughness, etc. of the composite material, and is also beneficial to improving the crack control ability of the composite material. The present invention controls the amount of coal gangue powder within the above range. When the amount of coal gangue powder is too high, the crack control ability of the composite material will be weakened, and cracks will exist on the surface of the obtained composite material; and, when the amount of coal gangue powder is too high, the mechanical properties of the composite material will be reduced.
[0011] The present invention controls the amount of fly ash within the above range. If the amount of fly ash is too much, the fly ash will be wrapped by the gel before it can react. The unreacted fly ash particles are large and have a smooth surface, and cannot be tightly bonded with the gel. In addition, after the slag and part of the fly ash react with the alkali activator first, the remaining excess fly ash will not have enough alkali activator to dissolve the aluminosilicate precursor, resulting in a large amount of [SiO 4 ] 4- and [AlO 4 ] 4- It cannot participate in the polymerization reaction and cannot generate more C(N)-ASH gel, resulting in a large amount of loose gel and unable to form a dense network structure.
[0012] The present invention controls the amount of slag within the above range. Although slag can promote the improvement of the axial tensile strength of the composite material, too much slag will consume too much alkali activator, which is not conducive to the reaction of other gelling materials, making other gelling materials unable to play a role. At the same time, it will also cause the subsequent added fibers to be difficult to stir and disperse. The composite material finally obtained is prone to internal structural defects, which not only wastes material resources, but also fails to achieve the expected composite material performance. In addition, the amount of slag has a significant effect on the axial compressive strength of the composite material, because the calcium ions contained in the slag play a key role in promoting the formation of CASH gel, and CASH gel is more conducive to forming a denser structure, thereby improving the axial compressive strength.
[0013] Preferably, the amount of quartz sand is 20% of the mass of the cementitious material, the amount of the alkali activator is 40% of the mass of the cementitious material, the amount of the fiber is 2% of the volume of the alkali-activated composite material, the amount of the retarder is 1% of the mass of the cementitious material; the amount of water is used to control the water-cement ratio to 0.3.
[0014] Preferably, the SiO in the coal gangue powder 2 The mass content is 44-46%, Al 2 O 3 The mass content is 34-36%.
[0015] More preferably, the coal gangue powder is coal gangue powder calcined at 700-800°C.
[0016] The present invention adopts high-temperature calcined coal gangue powder, which has strong activity and can promote the formation of CASH (hydrated calcium aluminosilicate) gel and NASH (hydrated sodium aluminosilicate) gel, thereby increasing the strength and density of the composite material.
[0017] More preferably, the particle size of the coal gangue powder is D50=45 μm.
[0018] Preferably, the SiO in the fly ash 2 The mass content of Al is 52-55%, 2 O 3 The mass content is 30-32%.
[0019] Preferably, the mass content of CaO in the slag is 33-35%, and the mass content of SiO 2 The mass content of Al is 34-35%, 2 O 3 The mass content is 16-18%.
[0020] The coal gangue powder in the present invention is a silicon-aluminum material, the fly ash is a silicon-aluminum material, and the slag is a calcium-silicon-aluminum material. The CaO in the slag can react with different monomers (such as silicate monomers and aluminate monomers) to form different reaction products. A part of the CaO reacts with the dissolved silicate and aluminate to form CSH and CASH gels, and a part of the Na + Replace Ca 2+ NASH gel is formed.
[0021] Preferably, the particle size of the quartz sand is 76-150 μm and the density is 2.65 g / cm 3 .
[0022] Preferably, the alkaline activator is a mixture of sodium silicate solution and NaOH solution.
[0023] More preferably, the Baume degree of the sodium silicate solution is 50, the concentration of the NaOH solution is 10 mol / L; and the mass ratio of the sodium silicate solution to the NaOH solution is 1:2.
[0024] Preferably, the fiber is a polyethylene fiber; the polyethylene fiber has a length of 12 mm and a diameter of 12 μm.
[0025] Preferably, the retarder is barium chloride particles.
[0026] The present invention also provides a method for preparing the gangue-slag-fly ash based alkali activated composite material according to the above technical solution, comprising the following steps:
[0027] (1) mixing coal gangue powder, fly ash, slag, quartz sand and retarder, and then adding alkali activator and water at the same time, and stirring to obtain a coal gangue-slag-fly ash-based alkali activated matrix;
[0028] (2) The gangue-slag-fly ash-based alkali-activated matrix obtained in step (1) is mixed with fibers, and subjected to film coating and water immersion curing to obtain the gangue-slag-fly ash-based alkali-activated composite material.
[0029] Compared with the prior art, the present invention has the following advantages and technical effects:
[0030] The present invention uses coal gangue powder, fly ash, slag, quartz sand, alkali activator, fiber, retarder and water as raw materials; the coal gangue powder has volcanic ash effect and micro-aggregate effect, which not only increases the number and bonding energy of hydration products in the composite material, makes a large number of pores tend to "spherical" or "arched" stress characteristics, and enhances the stress characteristics of internal pores, but also the addition of coal gangue powder helps to fill the gap between the fiber and the matrix, so that in the process of crack expansion to instability, the bonding force between the fiber and the matrix is greater than the tensile strength of the fiber, thereby effectively improving the ductility of the composite material; the slag has high reactivity and can form a denser matrix in an alkaline environment, thereby improving the bonding force between the matrix and the fiber, reducing the proportion of the fiber pull-out failure mode, thereby improving the axial tensile limit strain of the composite material. Fly ash and coal gangue powder generate a large amount of Al-SH and NASH gel under the action of alkali activator, which are then interwoven with a small amount of CASH generated by slag to form a better network structure, playing a good synergistic role and improving the mechanical properties of the composite material. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] The drawings constituting a part of the present application are used to provide a further understanding of the present application. The illustrative embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:
[0032] Figure 1 The particle size distribution curves of coal gangue powder, fly ash, slag and quartz sand in Example 1 and Comparative Examples 1-9 are shown;
[0033] Figure 2 The microscopic morphology of the coal gangue powder in Example 1 and Comparative Examples 1-9;
[0034] Figure 3 The microscopic morphology of fly ash (a) and slag (b) in Example 1 and Comparative Examples 1-9;
[0035] Figure 4 A schematic diagram of the process of designing the mix ratio of the gangue-slag-fly ash based alkali activated composite material by using the simplex centroid enhancement design method of the present invention;
[0036] Figure 5 Specimen dimensions and test setup adopted for axial tension performance testing;
[0037] Figure 6 The axial tensile failure mode diagram of the composite materials prepared in Example 1 and Comparative Examples 1-9;
[0038] Figure 7 The stress-strain curves of the axial tensile test of the composite materials prepared in Example 1 and Comparative Examples 1-9;
[0039] Figure 8 Specimen dimensions and test setup diagram for axial compression performance tests;
[0040] Fig. 9 axial compression failure mode diagram of the composite materials prepared in Example 1 and Comparative Examples 1-9;
[0041] Fig.10 The stress-strain curves of the axial compression test of the composite materials prepared in Example 1 and Comparative Examples 1-9;
[0042] Fig.11 A physical picture of the jump platform for measuring the expansion (left) and the method for measuring the expansion (right);
[0043] Fig.12 The fluidity bar graph of the composite materials prepared in Example 1 and Comparative Examples 1-9;
[0044] Fig.13 Diagram of specimen dimensions and test setup used for fracture properties testing;
[0045] Fig.14 The P-δ curves of the composite materials prepared in Example 1 and Comparative Examples 1-9;
[0046] Fig.15 The P-CMOD curves of the composite materials prepared in Example 1 and Comparative Examples 1-9 are shown. DETAILED DESCRIPTION
[0047] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0048] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.
[0049] In the embodiments of the present invention, normal temperature refers to "25±2°C".
[0050] Unless otherwise specified, the raw materials in the examples of the present invention were purchased from commercial sources.
[0051] In the following examples, the gangue powder comes from Lingshou County, Hebei Province, the fly ash comes from Beishankou Town, Gongyi City, Henan Province, the slag comes from Beishankou Town, Gongyi City, Henan Province, the sodium silicate solution comes from Jiaxing Yourui Refractory Materials Co., Ltd., and the fiber comes from DSM.
[0052] Example 1 and Comparative Examples 1-9
[0053] A gangue-slag-fly ash-based alkali-activated composite material. The raw materials for preparing the gangue-slag-fly ash-based alkali-activated composite material are gangue powder, fly ash, slag, quartz sand, alkali activator, fiber, retarder and water. The gangue powder, fly ash and slag constitute a cementitious material. The amount of quartz sand is 20% of the mass of the cementitious material, the amount of the alkali activator is 40% of the mass of the cementitious material, the amount of the fiber is 2% of the volume of the alkali-activated composite material, and the amount of the retarder is 1% of the mass of the cementitious material. The amount of water is to control the water-binder ratio to be 0.3. The alkali activator is a mixture of sodium silicate solution and NaOH solution, the Baume degree of the sodium silicate solution is 50, the concentration of the NaOH solution is 10 mol / L, and the mass ratio of the sodium silicate solution to the NaOH solution is 1:2. The gangue powder is the gangue powder calcined at 700°C.
[0054] The chemical compositions of coal gangue powder, fly ash and slag are shown in Tables 1-2 and 4, and the parameters of fly ash, slag, sodium silicate solution and polyethylene fiber are shown in Tables 3 and 5-7; the raw material compositions of Example 1 and Comparative Examples 1-9 are shown in Table 9;
[0055] The preparation process is:
[0056] (1) putting coal gangue powder, fly ash, slag, quartz sand and barium chloride particles into a mixer and stirring for 2 minutes, scraping the wall of the stirring pot and stirring for another 2 minutes, then adding an alkali activator and ice water and stirring for 2 minutes with a mixer, scraping the wall again, and finally stirring for 1 minute to obtain a coal gangue-slag-fly ash-based alkali-activated matrix;
[0057] (2) The clumped polyethylene fibers are fully blown away, and then mixed with the gangue-slag-fly ash-based alkali-activated matrix obtained in step (1), stirred with a stirrer for 2 minutes, and then the wall of the stirring pot is scraped, and then stirred with a stirrer for another minute, placed in a mold, coated and cured at room temperature for 24 hours, the film is removed, and the mixture is immersed in water at room temperature and sealed for curing for 28 days to obtain a gangue-slag-fly ash-based alkali-activated composite material.
[0058] Table 1 Chemical composition of coal gangue powder (unit: %)
[0059]
[0060] Table 2 Chemical composition of fly ash (unit: %)
[0061]
[0062] Table 3 Physical parameters of fly ash
[0063]
[0064] Table 4 Chemical composition of slag (unit: %)
[0065]
[0066] Table 5 Physical parameters of slag
[0067]
[0068] Table 6 Parameters of sodium silicate solution
[0069]
[0070] Table 7 Parameters of polyethylene fiber
[0071]
[0072] Figure 1 The particle size distribution curves of coal gangue powder, fly ash, slag and quartz sand in Example 1 and Comparative Examples 1-9 are shown in FIG. Figure 1 It can be seen that the particle size of coal gangue powder is D50=45μm, the particle size distribution of fly ash is 4-66μm, the particle size distribution of slag is 2-24μm, and the particle size distribution of quartz sand is 76-150μm.
[0073] Figure 2 The microscopic morphology of the coal gangue powder in Example 1 and Comparative Examples 1-9 is shown in FIG. Figure 2 It can be seen that the coal gangue powder used in the present invention is in the form of irregular wrinkles, flakes or blocks in a microscopic state, with micron-level or even nano-level minerals attached to the surface, and some tiny pores, which can increase the specific surface area.
[0074] Figure 3 The microscopic morphology of fly ash (a) and slag (b) in Example 1 and Comparative Examples 1-9. Figure 3 It can be seen that the fly ash used in the present invention is spherical in microscopic state, and the slag is irregular block in microscopic state.
[0075] The present invention calculates the upper and lower limits of gangue powder, fly ash and slag with the help of pseudo components. According to the simplex centroid axis point enhancement design method, the pseudo components are converted into actual components to obtain 7 mix ratio designs, and 3 axial points are added. The results are shown in Figure 4 .according to Figure 4 The usage ratio of coal gangue powder, fly ash and slag in the composite material was obtained, and each group was numbered. The results are shown in Table 8.
[0076] Table 8 The ratio of coal gangue powder, fly ash and slag in the composite material obtained by the simplex centroid reinforcement design method
[0077] Point Type Test No. slag Fly ash Coal Gangue Powder Vertex 1 S50FA50 0.5 0.5 0 Vertex 2 S20FA50CG30 0.2 0.5 0.3 Vertex 3 S20FA80 0.2 0.8 0 Mixing point 4 S40FA55CG5 0.4 0.55 0.05 Mixing Point 5 S25FA55CG20 0.25 0.55 0.2 Mixing point 6 S25FA70CG5 0.25 0.7 0.05 Centroid 7 S30FA60CG10 0.3 0.6 0.1 Axial point 8 S35FA50CG15 0.35 0.5 0.15 Axial point 9 S35FA65 0.35 0.65 0 Axial point 10 S20FA65CG15 0.2 0.65 0.15
[0078] Note: In the number, S stands for slag, FA stands for fly ash, and CG stands for coal gangue powder. Taking S20FA50CG30 as an example, it means that the mass proportion of slag S is 20%, the mass proportion of fly ash FA is 50%, and the mass proportion of coal gangue powder CG is 30%.
[0079] According to the weight of each component in Table 8, the water-binder ratio of all composite materials was set to 0.3, thereby obtaining the raw material composition of each embodiment and comparative example. The results are shown in Table 9.
[0080] Table 9 Raw material composition of Example 1 and Comparative Examples 1-9
[0081]
[0082]
[0083] Performance Testing
[0084] (1) Axial tensile performance: Axial tensile performance tests and result evaluation were carried out in accordance with JC / T 2461-2018 “Test methods for mechanical properties of high ductility fiber reinforced cementitious composites”.
[0085] The specimen size is 330mm×60mm×13mm dumbbell type, and the number of specimens in each group is 3. The displacement control loading is carried out using a WMATEST C088-01 electronic universal testing machine with a displacement control speed of 0.5mm / min. The specimen size and test settings used in the test are shown in Figure 5 The test load was collected by the force sensor of the testing machine. At the same time, linear displacement meters (LVDTs) were set at both ends of the specimen. The collection frequency was set to 50 Hz. The deformation of the 80 mm measuring section in the middle of the specimen was collected. The test results are shown in Figure 6-7 and Table 10.
[0086] The calculation formula of the ultimate tensile stress is:
[0087]
[0088] In the formula, σ tu Indicates the ultimate tensile stress (MPa), F tu Indicates the maximum tensile force (N) that the specimen can withstand, A t Indicates the initial cross-sectional area of the specimen deformation measurement area (mm 2 ).
[0089] Figure 5 Specimen dimensions and test setup adopted for axial tension testing.
[0090] Figure 6 The axial tensile failure mode diagram of the composite materials prepared in Example 1 and Comparative Examples 1-9. Figure 6 It can be seen that after the specimens were damaged by loading, since the main damage of the specimens after being stressed was concentrated in the middle of the specimens, one of each group was randomly selected as a typical failure mode, and its failure morphology was mainly manifested in the increase in the number of cracks and crack width of the specimens. The specimens were in the elastic stage at the initial loading. As the load increased until the cracking load, cracks first appeared in the middle position, but did not lead to brittle failure. This was due to the addition of PE fibers, which achieved the transition from brittle to ductile by bridging the cracks. As the load value further increased, cracks appeared one by one accompanied by the sound of the matrix breaking. In the later stage of axial tension, the number of cracks tended to stabilize. As the crack width increased, the fibers continued to be pulled out or broken, and finally formed a main crack in the middle of the specimen, in which the fibers were connected like broken threads. Even at the end of loading, the specimen remained intact due to the complex spatial grid structure formed by the internal fibers. This structure reinforced each other and gave full play to the role of PE fibers.
[0091] Figure 7 The stress-strain curves of the axial tensile test of the composite materials prepared in Example 1 and Comparative Examples 1-9 are shown in FIG. Figure 7 It can be seen that the stress-strain curves of all specimens have similar three stages of development, including elasticity, stiffness softening and pseudo-strain-hardening. First, the axial tensile load in the elastic stage is mainly borne by the matrix. Secondly, the sliding of the interface between the PE fiber and the matrix causes the axial tensile stiffness to decrease, and then enters the stiffness softening stage. Finally, in the pseudo-strain-hardening stage, the fiber bridging effect is fully activated. As the strain continues to increase, the stress growth rate slows down until the fiber is pulled out and the bridge fails. The strain range of all specimens is 2.97-9%, of which 9 composites meet the ductility requirements with strains exceeding 3%. Among all composite materials, S30FA60CG10 has the highest axial tensile strain, reaching an ultimate strain of 8.37%, while S25FA70CG5 has the lowest strain, with an ultimate strain of only 2.97%. The axial tensile strength of all specimens is between 4.5-10MPa, with good axial tensile strength. Among them, S40FA55CG5 has the highest ultimate tensile stress, reaching 9.75MPa, while S20FA80 has the lowest ultimate tensile stress, which is 4.54MPa, an increase of 1.15 times. The lowest initial crack stress of all specimens is 2.57MPa for S20FA80, with a corresponding initial crack strain of 0.146%, and the highest initial crack stress is 5.31MPa for S40FA55CG5, with a corresponding initial crack strain of 0.23%, an increase of 1.07 times and 0.58 times, respectively.
[0092] Table 10 Axial tensile properties of Example 1 and Comparative Examples 1-9
[0093]
[0094]
[0095] Note: The data in brackets in the table are standard deviations of the test values.
[0096] It can be seen from Table 10 that the development law of axial tensile toughness is similar to that of deformation capacity. Overall, axial tensile toughness is mainly affected by the slag content. However, under the same slag content, as the proportion of coal gangue powder increases, the axial tensile toughness can also be improved, such as S20FA65CG15 compared with S20FA80, which is 12.7% higher, but when the proportion of coal gangue powder increases more, such as S20FA50CG30, it is only 5.10% higher than S20FA80.
[0097] (2) Axial compression performance: The test and result evaluation are carried out in accordance with CECS13:2009 "Fiber Concrete Test Method Standard" and ASTM C469 cylindrical axial compression test method.
[0098] The designed specimen size is a φ50mm×100mm cylinder, and the number of specimens in each group is 3. A WMATEST C088-01 voltage servo testing machine with a displacement control speed of 0.12mm / min is used for displacement-controlled loading, and a TDS-540 model high-speed static strain gauge is used for synchronous data acquisition with an acquisition frequency of 50Hz. To prevent the application of bias, the top and bottom of the specimen need to be plastered and kept level, and then left in a cool place for 24 hours before the experiment. A ferrule is used to fix the linear displacement sensors (LVDTs) at both ends of the specimen to monitor the deformation of the specimen. The specimen size and axial pressure settings used in the test are as follows: Figure 8 To avoid damage to the specimen due to overload, the press is set to automatically unload when the load drops to 80% of the peak load. Figure 9-10 and Table 11.
[0099] The elastic modulus is calculated as follows:
[0100]
[0101] In the formula, E represents the elastic modulus, σ 2 Indicates the stress corresponding to 40% of the maximum load, σ 1 Indicates the stress corresponding to axial strain of 0.005%, ε c Represents σ 2 The corresponding axial strain.
[0102] Figure 8 Diagram of the specimen dimensions and test setup used for the axial compression performance test.
[0103] Fig. 9 The axial compression failure mode diagram of the composite materials prepared in Example 1 and Comparative Examples 1-9. Fig. 9 It can be seen that after the specimens were loaded with axial compression, the middle of any one of the three specimens in each group was taken as a typical failure mode. Under the action of the fiber, the crack width in the matrix was effectively controlled, so that the specimen showed ductility performance beyond ordinary concrete under axial compression. Compared with ordinary concrete that is easy to break, the composite material can maintain a high structural integrity when it fails, which is attributed to the fiber's ability to limit crack expansion. The microcracks of the specimen continued to increase and expand with the continuous increase of axial pressure. After activating the bridging effect of the fiber, the inside of the specimen obtained a lateral constraint, so that the cracks of the specimen were limited to a smaller size range, avoiding the sudden crushing of the specimen. After unloading, the specimen was observed as a whole, and it can be found that there are many microcracks distributed around the main crack of the specimen, which reflects a good stress state as a whole. At the same time, it can be seen that all specimens can be divided into three types of failure modes after the axial compression test: (1) For the two groups of S40FA55CG5 and S50FA50 with an axial compression ultimate strength greater than 90 MPa, the strength is relatively high. Thin and short cracks begin to appear on the middle surface of the specimen. As the load continues to increase, the main crack forms and develops along the vertical axis until it penetrates the entire specimen. There is basically no fragmentation and the overall tensile damage is obvious; (2) For the two groups of S20FA80 and S20FA50CG30 with relatively low axial compression strength, the specimens show oblique crack shear failure, and the main crack The cracks are inclined at a certain angle to the vertical axis of the specimen; (3) For specimens of other groups, multiple intersecting cracks appear after the specimens are subjected to compressive loads, which roughly show "y" or "x" shaped failure. This failure feature is between shear failure and tension failure. At the same time, many small fragments will be broken off from the surface of the specimen during failure, and even bulges will protrude laterally, such as S20FA65CG15 and S20FA50CG30 in the figure. This may be due to the low slag content and the lack of calcium ions to promote the formation of CASH (hydrated calcium silicate aluminate) gel. Therefore, the matrix is relatively sparse and not dense.
[0104] Fig.10 The stress-strain curves of the axial compression test of the composite materials prepared in Example 1 and Comparative Examples 1-9 are shown in FIG. Fig.10It can be seen that the lowest axial compressive strength is 66.61MPa of S20FA50CG30, and the highest is 109.55MPa of S50FA50, which is an increase of 64.5%. In contrast, if ordinary concrete is compressed to reach peak strength, the matrix will directly crack into pieces, showing obvious brittle failure, and the image curve stress will directly drop to 0, and it is impossible to form an extended section like the fiber-reinforced alkali-activated composite material, thanks to the bridging ability of PE fibers. Unlike ordinary concrete, the residual stress strength of the composite material still shows a relatively high state after the strain exceeds 0.015%, which reflects the excellent post-peak ductility of the composite material. Comparing the three groups of images of S20FA80, S20FA50CG30 and S20FA65CG15, it can be clearly observed that when the slag content is low, as the content of coal gangue powder increases, although the axial compressive strength of the material will increase first and then decrease, it will not be lower than the strength of the composite material without coal gangue powder, and it can also effectively reduce the phenomenon of the axial compressive strength dropping sharply after the curve reaches the peak point. This shows that at low slag content, adding an appropriate amount of coal gangue powder can not only improve the axial compressive strength of the material, but also alleviate the brittleness of the material to a certain extent. In contrast, from the three groups of images of S50FA50, S20FA50CG30 and S35FA50CG15, it can be clearly observed that with the increase of slag content, the axial compressive strength of the material will have a more obvious increase, which shows that the size of the axial compressive strength of the material still depends on the slag content to a large extent.
[0105] Table 11 Axial compression properties of Example 1 and Comparative Examples 1-9
[0106]
[0107]
[0108] Note: The data in brackets in the table are standard deviations of the test values.
[0109] It can be seen from Table 11 that the development law of elastic modulus is basically the same as the change law of axial compressive strength. The change of elastic modulus is obviously affected by the change of slag proportion. As the slag content decreases, the elastic modulus gradually decreases. When the slag content remains unchanged, with the increase of gangue powder proportion, the elastic modulus increases, such as S20FA65CG15 increases by 5.5% relative to S20FA80, and S35FA50CG15 increases by 1.9% relative to S35FA65. However, with the continued increase of gangue powder proportion, the elastic modulus decreases, such as S20FA50CG30 decreases by 10.9% relative to S20FA80. In other words, increasing the gangue powder content appropriately is beneficial to the improvement of elastic modulus.
[0110] (3) Liquidity
[0111] According to the requirements of GB / T 2419-2005 "Test method for fluidity of cement mortar", the composite material is tested for fluidity and the results are evaluated.
[0112] The jumping table test method is adopted, and a cone mold with an upper diameter of 70mm, a lower diameter of 100mm and a height of 60mm is used as the test specimen. The expansion is used to measure the fluidity of the composite material. The vibration frequency is 1 time / 1min. After waiting for 25 seconds to end the jumping table work, the cone is quickly lifted vertically, and the two diameter lengths are measured with a 90° L-shaped angle ruler, and the average value is taken as the expansion.
[0113] Fig.11 A physical picture of the platform for measuring the expansion (left) and the method for measuring the expansion (right).
[0114] Fig.12 The fluidity bar graph of the composite materials prepared in Example 1 and Comparative Examples 1-9. Fig.12 It can be seen that the fluidity of different composite materials does not change much, and the highest fluidity is 167mm for S20FA80. From the overall data, it can be observed that with the increase of coal gangue powder content, the fluidity gradually decreases. This may be because coal gangue powder absorbs a large amount of water. Therefore, during the mixing process, coal gangue powder absorbs a large amount of mixing water. The reduction of water leads to poor dispersion of powder particles, which leads to a decrease in fluidity.
[0115] (4) Fracture performance: The test and the fracture performance results of the specimens were evaluated according to the specification JCI-S-001-2003 "Method of test for fracture energy of concrete by use of notched beam".
[0116] The specimen design size is a notched beam of 40mm×40mm×160mm, and the number of specimens in each group is 3. A WMATEST C088-01 electronic universal testing machine with a displacement control speed of 0.1mm / min is used for displacement control loading, and a TDS-540 model high-speed static strain gauge is used for data synchronization acquisition. Displacement meters (LVDT) are set on both sides of the specimen to measure the mid-span deflection with an accuracy of 0.01mm. The specimen size and test settings of the test are as follows: Fig.13 As shown, the distance between the two lower supports is 120 mm, and the distance between the supports and the edge of the specimen is 20 mm. At the same time, both fulcrums use horizontally movable roller devices to avoid horizontal constraints during the fracture test. In addition, before loading, the bottom surface of the specimen is pasted with a metal blade sheet to fix the extensometer, which is convenient for measuring the change in the incision width of the specimen.
[0117] Fig.13 Diagram of the specimen dimensions and test setup used for the fracture properties tests.
[0118] Fig.14 The P-δ curves of the composite materials prepared in Example 1 and Comparative Examples 1-9 are shown in FIG. Fig.14 It can be seen that the average cracking load of the specimens is between 0.3 and 1.1 kN, the minimum cracking load is 0.24 kN for S20FA50CG30, and the maximum cracking load is 1.08 kN for S40FA55CG5, which is an increase of 3.5 times.
[0119] Fig.15 The P-CMOD curves of the composite materials prepared in Example 1 and Comparative Examples 1-9 are shown in FIG. Fig.15 It can be seen that the gangue-slag-fly ash-based alkali-activated composite material provided by the present invention has ductile failure characteristics. The cracking CMOD of the specimen is between 0.04-0.32mm, the smallest is 0.04mm for S25FA55CG20, and the largest is 0.316mm for S40FA55CG5. The average peak load of all groups is between 1.0-2.5kN, the smallest is 1.136kN for S20FA65CG15, and the largest is 2.297kN for S40FA55CG5, which is 1.02 times higher. Correspondingly, the CMOD is in the range of 1-6.2mm, the smallest is 1.3mm for S30FA60CG10, and the largest is 6.187mm for S35FA50CG15.
[0120] (5) Fracture energy: The fracture energy is tested according to JCI-S-001-2003 “Method of test for fracture energy of concrete by use of notched beam”.
[0121] The fracture energy is determined by the load P-CMOD curve of the notched beam under three-point loading, and the results are shown in Table 12.
[0122] The calculation formula of fracture energy is:
[0123]
[0124] Where W 1 It represents the sum of the work done by the deadweight of the specimen and the deadweight of the fixture; Indicates the ratio of the span between two points to the length of the specimen; m 1 Indicates the deadweight of the specimen; m 2 Indicates the weight of the fixture that can be freely twisted on the testing machine, usually m 2=0; g represents the acceleration due to gravity, which is 9.81m / s 2 ; G F W represents fracture energy; 0 Represents the work done by external force; A lig represents the cross-sectional area of the beam above the notch (depth is 24 mm, width is 40 mm). In addition, for a three-point bending notched beam, the work done by the external force during the fracture process is W 0 It is calculated as the area under the P-CMOD curve. Because the composite material has good ductility, it is difficult for the curve to reach the zero point completely. Therefore, it is stipulated here that the load is reduced to 30% of the maximum load as the standard. At this time, the corresponding CMOD is CMOD 0 .
[0125] Table 12 Fracture energy of Example 1 and Comparative Examples 1-9
[0126]
[0127]
[0128] Note: The data in brackets in the table are standard deviations of the test values.
[0129] It can be seen from Table 12 that with the increase of slag content, the fracture energy of the composite material increases accordingly, especially when the addition amount of coal gangue powder is about 5% (S40FA55CG5), the fracture energy of the specimen can reach 22.05 kJ / m 2 This result highlights the synergistic effect of the alkali-activated composite material composed of coal gangue powder, slag and fly ash in improving the fracture energy.
[0130] The above are only preferred specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.
Claims
1. A gangue-slag-fly ash based alkali activated composite material, characterized in that: The raw materials for preparing the gangue-slag-fly ash-based alkali-activated composite material include gangue powder, fly ash, slag, quartz sand, alkali activator, fiber, retarder and water; The coal gangue powder, fly ash and slag constitute a cementitious material; the cementitious material comprises 2.5-12% coal gangue powder, 52-58.3% fly ash and 36.5-43.2% slag by mass percentage; The amount of quartz sand is 20% of the mass of the cementitious material, the amount of the alkali activator is 40% of the mass of the cementitious material, the amount of the fiber is 2% of the volume of the alkali-activated composite material, and the amount of the retarder is 1% of the mass of the cementitious material; the amount of water is to control the water-binder ratio to 0.3; The alkaline activator is formed by mixing a sodium silicate solution and a NaOH solution; the Baume degree of the sodium silicate solution is 50, the concentration of the NaOH solution is 10 mol / L; and the mass ratio of the sodium silicate solution to the NaOH solution is 1:
2.
2. The gangue-slag-fly ash based alkali activated composite material according to claim 1, characterized in that: The mass content of SiO2 in the coal gangue powder is 44-46%, and the mass content of Al2O3 is 34-36%.
3. The gangue-slag-fly ash based alkali activated composite material according to claim 1, characterized in that: The mass content of SiO2 in the fly ash is 52-55%, and the mass content of Al2O3 is 30-32%.
4. The gangue-slag-fly ash based alkali activated composite material according to claim 1, characterized in that: The mass content of CaO in the slag is 33-35%, the mass content of SiO2 is 34-35%, and the mass content of Al2O3 is 16-18%.
5. The gangue-slag-fly ash based alkali activated composite material according to claim 1, characterized in that: The particle size of the quartz sand is 76-150 μm and the density is 2.65 g / cm 3 .
6. The gangue-slag-fly ash based alkali activated composite material according to claim 1, characterized in that: The fiber is polyethylene fiber; the polyethylene fiber has a length of 12 mm and a diameter of 12 μm.
7. The gangue-slag-fly ash based alkali activated composite material according to claim 1, characterized in that: The retarder is barium chloride particles.
8. The method for preparing the gangue-slag-fly ash based alkali activated composite material according to any one of claims 1 to 7, characterized in that: The following steps are involved: (1) mixing coal gangue powder, fly ash, slag, quartz sand and retarder, and then adding alkali activator and water at the same time, and stirring to obtain a coal gangue-slag-fly ash-based alkali activated matrix; (2) The gangue-slag-fly ash-based alkali-activated matrix obtained in step (1) is mixed with fibers, and subjected to film coating and water immersion curing to obtain the gangue-slag-fly ash-based alkali-activated composite material.
Citation Information
Patent Citations
Steel slag modified high-ductility geopolymer composite material as well as preparation method and application thereof
CN117003517A